Single fraction radiotherapy is more acceptable than multi-fraction radiotherapy to palliate the metastatic bone pain (Bangladesh Medical Journal, 2017)
One of the main goals of palliative radiation treatment is the relief of pain or dysfunction caused by the bone metastasis. Most patients achieve pain relief after irradiation. The striking clinical observation is that some patients experience symptom relief within 24hrs after the irradiation. This quasi experimental study was carried out in the department of Oncology, BSMMU from January 2014 to June 2014 with the intention to compare the role of single fraction and multiple fraction radiotherapy in the management of bone secondaries as regard as potency for pain relief. A total of 100 patients with age up to 70 years and of any sex having cytologically or histologically proven malignant diseases with the painful bone metastases in single or multiple sites without pathological fracture were selected for the study. They had no history of previous radiotherapy on the treatment site. Patients were divided in to two Arm A and Arm B with 50 patients in each arm. Arm A was treated with single (8 Gy) fraction radiotherapy and Arm B was treated with multiple fraction (30 Gy) radiotherapy i.e. 300 cGy per fraction in 10 fractions, 5 days a week for two weeks by telecobalt or orthovoltage machine. 44 patients in Arm A & 46 patients in Arm B completed the study. Onset of pain relief after completion of 4th week radiation were 68% in Arm A and 67.4% in Arm B . It was observed that, after 8th week of radiation 81.8% in Arm A and 86% in Arm B were relieved from pain. According to histological typing, 45% in Arm A & 52% patients in Arm B had complete response; 40% in Arm A & 37% patients in Arm B had partial response and overall distribution of no response of patient in Arm A was 18% and in Arm B was 7%. Metastatic bone pain represents one of the major indications in the external beam radiation therapy today.The disease can be efficiently treated by the use of either single fraction or multifraction radiotherapy without any significant difference in response to rate and early toxicities.Bangladesh Med J. 2016 Sep; 45 (3): 151-155